Burnout syndrome in medical professionals: a manifestation of chronic stress with counterintuitive passive characteristics - Ptacek, Radek; Stefano, George B; Kuzelova, Hana; Raboch, Jiri; Harsa, Pavel; Kream, Richard M (Neuro endocrinology letters, 2013)
By operational criteria, burnout appears to be a multifaceted behavioral syndrome consisting of maladaptive individual responses subsequent to prolonged stressful situations. Given the intense physical and cognitive demands of providing high quality healthcare to a wide spectrum of patients, healthcare professionals are particularly susceptible to developing burnout syndrome, a notable phenomenon that has gleaned significant societal attention in recent years. Clearly, widespread manifestation of burnout by health care professionals represents a serious potential threat to the overall quality of patient care and to the realization of positive outcomes to multiple treatment strategies. It will most certainly engender a serious negative impact on the economic viability of the entire healthcare system. Presently, our brief review focuses on current research efforts to 1) provide precise behavioral and psychiatric diagnostic criteria for burnout syndrome in healthcare professionals, 2) identify potential etiological factors and ongoing stressors, and 3) outline an integrative approach for treatment and prevention.
Keywords: Burnout, Professional; profesionální vyhoření; Humans; Health Personnel; zdravotnický personál; lidé